SWEATSHOPS AND CONSUMER CHOICES. (17th May 2018) - Ferguson, Benjamin; Ostmann, Florian
Abstract: We consider a case where consumers are faced with a choice between sweatshop-produced clothing and identical clothing produced in high-income countries. We argue that it is morally better for consumers to purchase clothing produced in sweatshops and then to compensate sweatshop workers for the difference between their actual wage and a fair wage than it is for them either to purchase the sweatshop clothing without this compensatory transfer or to purchase clothing produced in high-income countries.